Theatre as Contagion: Making Sense of Communication in Performative Arts - Sugiera, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Contagion is more than an epidemiological fact. The medical usage of the term is no more and no less metaphorical than in the entire history of explanations of how beliefs circulate in social interactions. The circulation of such communicable diseases and the circulation of ideas are both material and experiential. Diseases and ideas expose the power and danger of bodies in contact, as well as the fragility and tenacity of social bonds. In the case of the theatre, various tropes of contagion are to be found in both the fictional world on the stage (at least since Sophocles’ Oedipus Rex) and in many theories defining the rules of interaction between theatre audiences, fictitious characters and/or performers. In consequence, the historically changing concept of contagion has in many respects influenced how mimesis was conceived and understood. The main goal of my article is to demonstrate how the concept of contagion has changed over the last few decades and how it may influence our understanding of the idea of mimesis and participation in performative arts. This will be achieved in two steps. Firstly, I will compare the concept of contagion as the outbreak narrative that had influenced, among others, Antonin Artaud’s The Theater and the Plague with the more recent and dynamic concept of epidemic structured around the tipping point. Secondly, I will look for performative art forms with similar structure of audience responses, analyzing Mariano Pensotti’s project Sometimes I Think, I Can See You (2010), in order to demonstrate new forms of performativity and (re)presentation.